Metode Clustering Untuk Mengelompokan Titik Panas Bumi - Nasution, Wahyudi; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2022)
Some of the factors that cause forest and land fires are natural factors and human negligence. To determine areas prone to forest and land fires, namely by analyzing data mining techniques using the clustering method and k-means algorithm in order to find out the clustering rules between these clusters. The data processed is data as much as geothermal points obtained from the Manggala Agni Daops Sumatran XI / BTP which has been recapitulated from January to June and the variables used are id, level of confidence, satellite, probability radius and district. The potential for forest and land fires used is based on very vulnerable, prone and non-prone areas. With this analysis, information on areas that are prone to forest and land fires can be obtained and can help when carrying out integrated patrols and preventive patrols because it is known that areas prone to forest and land fires in the Manggala Agni Daops Sumatra XI / BTP work area, namely Tanjung Regency jabung timur and tanjung jabung barat.